2016
DOI: 10.1115/1.4032393
|View full text |Cite
|
Sign up to set email alerts
|

Tool Deflection Error of Three-Axis Computer Numerical Control Milling Machines, Monitoring and Minimizing by a Virtual Machining System

Abstract: Virtual manufacturing systems carry out the simulation of manufacturing processes in digital environment in order to increase accuracy as well as productivity in part production. There are different error sources in machine tools, such as tool deflection, geometrical deviations of moving axis, and thermal distortions of machine tool structures. The errors due to tool deflection are caused by cutting forces and have direct effects on dimensional accuracy, surface roughness of the parts, and efficient life of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Structural efficiency of a wind turbine blade is studied by Buckney et al [17] in order to improve designing process, minimizing weight and reducing the cost of wind energy. To analyze and modify the machining operations in virtual environments, virtual machining systems and applications is presented by Soori et al [18][19][20][21]. Virtual machining system and application is also presented by Altintas and Merdol [22] in order to obtain optimized condition of milling operations.…”
Section: -Review Of Research Work In the Deflection Errors Of Thin mentioning
confidence: 99%
“…Structural efficiency of a wind turbine blade is studied by Buckney et al [17] in order to improve designing process, minimizing weight and reducing the cost of wind energy. To analyze and modify the machining operations in virtual environments, virtual machining systems and applications is presented by Soori et al [18][19][20][21]. Virtual machining system and application is also presented by Altintas and Merdol [22] in order to obtain optimized condition of milling operations.…”
Section: -Review Of Research Work In the Deflection Errors Of Thin mentioning
confidence: 99%
“…Soori et al (2014) presented virtual machining by considering dimensional, geometrical and tool deflection errors in three-axis CNC milling machines in order to create actual machined parts in the virtual environments. Application of virtual machining systems in monitoring and minimising the tool deflection error of three-axis CNC milling machines is presented by Soori et al (2016).…”
Section: Review Of the Research Workmentioning
confidence: 99%
“…All of the research works on the tool deflection error presented so far have focused on the modelling as well as compensating the errors (Ratchev et al, 2003;Yun et al, 2002;Ikua et al, 2001;Habibi et al, 2011;Dépincé and Hascoët, 2006a). In order to decrease the tool deflection error in machining processes, optimisation techniques are also used in research works (Soori et al, 2016;Ong and Hinds, 2003;Merdol and Altintas, 2008). According to the author's findings, it was concluded that accuracy of the presented methods in tool deflection error modelling in comparison to the other methodologies were insufficiently explored in the previous works.…”
Section: Review Of the Research Workmentioning
confidence: 99%
“…Simulation techniques are becoming increasingly useful to help industries better manage their resources and not just for the educational benefit of the students. A method is provided for virtual machining which helps allocates errors in the design and manufacture of machine tools, diagnose the source of errors in machine tools and predict the accuracy of parts to be made on machine tools [10], [11]. The machining process and workpiece forming process can be observed directly in the virtual environment, so the correctness of the CAD/CAM code can be checked in advance to avoid the interference, collisions or other problems in the actual lathe processing and reduce the scrap rate of the workpiece and tool in the actual machining process.…”
Section: Introductionmentioning
confidence: 99%